Epidemiology of smoking among Kuwaiti adults: prevalence, characteristics, and attitudes - Anjum Memon; Philip M Moody; Thattaruparambil N. Sugathan; Najwa el-Gerges; Mahmoud al-Bustan; Ahmed al-Shatti; Hussain al-Jazzaf (The World Health Organization, 2000)
INTRODUCTION: In 1996 we conducted a cross-sectional survey to study the epidemiology of smoking among Kuwaiti adults. METHODS: The 4000 participants were selected using a three-stage stratified cluster sampling design. Altogether 3859 participants (1798 males, 2061 females) returned a completed self-administered questionnaire. RESULTS: The prevalence of smoking was 34.4% (95% confidence interval (CI) = 32.2-36.6) among men and 1.9% (95% CI = 1.3-2.5) among women. Among men, the highest prevalence (56.5%; 95% CI = 36.2-76.8) was observed in the youngest age group (< 20 years). Among women the highest prevalence was observed in one of the older age groups (46-50 years) (7.1%; 95% CI = 3.1-11.1). Multiple logistic regression analysis showed that the following factors were independently associated with smoking: lower levels of education (odds ratio (OR) 3.5; 95% CI = 1.5-8.4), lower employment grade (OR = 4.1; 2.5-6.7), and being a separated, divorced, or widowed woman (OR = 4.9; 95% CI = 2.0-11.8). The majority of smokers (68%) began smoking when younger than 20 years; significantly more men (70%) than women (33%) began smoking at these ages (P <0.0001). On average, men began smoking at an earlier age (18 years vs 21 years; P <0.001) and therefore had smoked for a longer period (15 years vs 12 years; P <0.05); men also consumed a higher number of cigarettes each day (26 vs 17; P <0.05). A large proportion of smokers were ignorant about the health consequences of passive smoking: about 77% of those with children reported that they smoked in the presence of their children. Almost half (47%) of all smokers stated that they wanted to stop smoking, and about 56% had attempted to quit. The biggest perceived barrier to quitting was uncertainty about ''how to quit''. A total of 338 respondents (8.8%; 95% CI = 5.8-11.9) were classified as former smokers. About half of the former smokers had quit between the ages of 20 and 29 years; the average age of quitting was 28 years. Former smokers were more likely to have smoked fewer cigarettes per day and to have smoked for significantly less time than current smokers. DISCUSSION: Given the fact that free education is provided at all levels by the government, anti-tobacco education and awareness should be included as an integral part of the curriculum in schools and colleges.